TIKTOK LIVE SHOPPING'S USE OF LIVE STREAMING TO INCREASE WORD OF MOUTH - Sonda, Ambun Salsabila Kandung; Balqiah, Tengku Ezni (Universitas Brawijaya, Indonesia, 2023)
Live streaming has become a well-liked way for businesses to boost interaction andÂ consumer engagement, ultimately leading to positive word-of-mouth promotion. Word of mouth is crucial in business since it serves as a reliable gauge for assessing a product's quality prior to purchase, hence reducing uncertainty in decision-making. Previous studies overlooked the benefits of live streaming for word-of-mouth. Â Hence, the objective of this study is to examine the emergence of word-of-mouth communication facilitated by live streaming, employing the socio-technical approach and attachment theory. This quantitative research has a total of 12 hypotheses. Data was collected through the distribution of online questionnaires using purposive sampling, by examined 319 TikTok Live Shopping users. The data was collected and analyzed using SmartPLS. Live streaming yields a favorable impact on user engagement and viral marketing. Streamers exert significant effect on audience engagement, fostering strong connections with the platform, user loyalty, and word-of-mouth promotion. Consequently, marketers can optimize the utilization of live streaming by collaborating with the most compatible streamers. Additionally, this study discovered that vicarious expression does not have a beneficial impact on platform attachment. This study suggests using live streaming as a strategy to improve customer retention and build stronger relationships with customers, which offers insightful information for business experts in Indonesia. It addresses the constraints of previous research, which focused mainly on loyalty to brands in terms of transactions, by providing theoretical support for exploring the relationship between user stickiness and word-of-mouth generation on live streaming platforms.